INVESTIGATION OF TRANS-POLAR H. F. RADIO PROPAGATION. - Schrader,David H.; Huang,George (1966)
A study of polar propagation of HF radio signals from Andoya, Norway, and from Thule, Greenland, to Pullman, Washington, was conducted. The signals were generated by step-frequency sounders operating from 4 MHz to 32 MHz. The study consisted of a study of the regular diurnal and seasonal variations of the MOF and LOF and a study of the effects of solar flares on the reception. During periods when the ionsphere is disturbed by particle flux from solar flares, the MOF decreases initially and the LOF increases some nine hours later on the average. Reception of signal is often lost during periods of either visual or radio aurora. The Andoya-Pullman path was more sensitive to such disturbances than the Thule-Pullman path. The MOF correlates negatively with the daily magnetic K sub p indices of the preceding day. (Author)